A conceptual framework for orthotic and prosthetic education. (August 2019) - Spaulding, Susan E; Yamane, Ann; McDonald, Cody L; Spaulding, Scott A
Background: Variables that influence orthotic and prosthetic patient outcomes beyond direct care are poorly conceptualized for orthotic and prosthetic students. Restructuring educational curricula around important clinical reasoning variables (i.e. factors that may influence outcomes) could improve teaching, learning, and clinical practice. Objectives: To propose an orthotic and prosthetic education framework to enhance the development of orthotic and prosthetic students' clinical reasoning skills. Study Design: Scoping review. Methods: We conducted a scoping review, identified variables of orthotic and prosthetic usability, and performed a qualitative thematic analysis through the lens of orthotic and prosthetic clinical educators to develop a conceptual framework for orthotic and prosthetic education. Results: Sorting of variables identified from the literature resulted in three thematic areas: (1) the state of functioning, disability, and health (International Classification of Functioning, Disability and Health); (2) orthotic and prosthetic technical properties, procedures, and appropriateness; and (3) professional service as part of orthotic and prosthetic interventions. The proposed orthotic and prosthetic education framework includes these three areas situated within the context of patient-centered care. Conclusions: A conceptual framework was developed from variables identified in peer-reviewed literature. This orthotic and prosthetic education framework provides a structure to explore orthotic and prosthetic clinical reasoning and advance our teaching and assessment of students' clinical reasoning skills. Clinical Relevance: The proposed orthotic and prosthetic (O&P) education framework is intended to promote conversation about variables (e.g. health condition, procedures, services, and O&P principles) that influence O&P clinical practice outcomes and further advance our teaching and assessment of students' clinical reasoning skills.